Esfarelamento do dualismo digital na contemporaneidade: uma leitura tecnodiscursiva - Sousa, Carlinho Viana de (Universidade Federal de São Carlos, 2025)
The discourses formulated, constituted, and circulated in the web environment are posing methodological, epistemological, and scientific challenges to traditional Discourse Analysis. This work is situated within the field of Digital Discourse Analysis, aiming to examine digital discourses native to the web—technodiscourses—where the "techno" and the "discursive" are two inseparable, co-constituted elements. To separate them implies a digital dualism: on one side, machines (the virtual world); on the other, humans (the real world)—that is, two distinct realities. With the goal of adopting a technodiscursive approach, we analyzed a multifaceted research corpus composed of the film The Emoji Movie, online comments about the film, and the analytical human-machine interaction with ChatGPT AI. Two approaches were employed: pre-digital and digital. In the pre-digital approach, grounded in Maingueneau’s enunciative theory and intersecting with theorists who discuss digital dualism, we examined the crumbling of boundaries between the real and the virtual. This stage of the research revealed that when people are offline, digital dualism still persists in some form; however, when they are online, this dualism begins to disintegrate, liquefy, and hybridize. They participate in a simulated society, where software (in this case, emojis) simulates human life. In the digital approach, the corpus was analyzed by the ChatGPT AI in a process of technodiscursive co-construction, in which human and machine, connected, produced discourse and cognition within an online environment. This reflects an ecological approach to discourse, aligned with the main argument of this thesis: that the process of technodiscursive co-construction gives rise to a simulated society, where humans, machines, software, and digital environments co-produce integrated, multiple discourses and cognitions—all deeply intertwined with the most essential technology: language.
The crumbling of digital dualism in contemporaneity: a technodiscursive reading
Keywords: Dualismo digital; Tecnodiscurso; Sociedade simulada; Digital dualism; Technodiscourse; Simulated society; CIENCIAS HUMANAS::EDUCACAO